Spectroscopic studies on inclusion properties of fullerenocalix[4]arene conjugates with metal ions - Luo, Chuping; Guldi, Dirk Michael; Soi, Antonio; Hirsch, Andreas (Journal of Physical Chemistry A, 2005)
Metal-chelating properties - in the ground and excited states - of fullerenocalix[4]arenes containing two malonamide substituents at the upper rim and four alkyl ester chains at the lower rim have been studied by means of steady-state absorption, fluorescence spectroscopy, and time-resolved transient absorption spectra. In particular, the influence that Ag enforces on the fullerene electronic spectra is due to direct interactions between Ag and the surface of C . The effects stemming from Na , Mg , and Ba , on the other hand, are indirect and are introduced through chelating the metal ions to the calix[4]arene moiety. They strongly depend on the molecular structure of the fullerenocalix[4]arenes. No spectroscopic evidence was obtained for any influence caused by Mn , although the malonamide groups provide good chelating ability even for this transition metal ion. © 2005 American Chemical Society.